Fast in the Ice: Adventures in the Polar Regions - Ballantyne, R. M. (Robert Michael), 1825-1894 (Salt Lake City, UT : Project Gutenberg, 2007)
"Fast in the Ice: Adventures in the Polar Regions" by R. M. Ballantyne is a novel written in the mid-19th century. The story follows Captain Harvey and the crew of the brig Hope as they embark on an expedition to the Arctic, driven by the desire to discover a supposed ice-free passage near the North Pole. As they venture into the icy wilderness, they encounter various challenges, from being trapped in ice for several years to facing polar bears and learning from the native Esquimaux about survival in the harsh conditions. The opening of the novel sets the stage for the crew's ambitious journey into the Arctic. The account begins with their departure from England, filled with high hopes and the looming dangers that await them. Captain Harvey is depicted as a strong-willed leader entangled in thoughts of leaving loved ones behind, signifying the emotional conflicts faced by the expedition members. As they press forward, the brig becomes icebound, initiating a struggle for survival that includes encounters with scurvy, stark encounters with wildlife, and the crew's dynamic as they attempt to understand and adapt to the life-threatening challenges of the polar terrain. The groundwork for their adventures, camaraderie, and eventual trials in the unforgiving ice is intricately established, promising readers an exploration of human endurance and the allure of the unknown. (This is an automatically generated summary.)
Release date is 2007-11-15
Produced by Nick Hodson of London, England
Keywords: Eskimos -- Juvenile fiction; Sailors -- Juvenile fiction; Survival skills -- Juvenile fiction; Polar regions -- Juvenile fiction; Explorers -- Juvenile fiction